ANALISIS POTENSI KEBANGKRUTAN PADA PERUSAHAAN PENERBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sylvester Sesa Langoday; Muh. Sabir (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2020)
Generally,bankruptcy is interpreted as a failure of the company in carrying out operations to achieve the goals. The purpose of this study was to determine the bankruptcy potential and comparison of bankruptcy potential between PT Airasia Indonesia Tbk and PT Indonesia Transport and Infrastructure Tbk.The type of data used in this study is quantitative data and qualitative data. Technique to collect the data is documentation.The analytical tool used is Altman Z-Scoreanalysis, Springate Score analysis and Zmijewski Scoreanalysis. The results from this study showed that:(1) Both of companies, PT Airasia Indonesia Tbk and PT Indonesia Transport and Infrastructure Tbk, are in the bankruptcy potential zone. (2) PT Airasia Indonesia Tbk has more potential for bankruptcy than PT Indonesia Transport and Infrastructure Tbk